How coach leadership is related to the coach-athlete relationship in elite sport - López de Subijana, C.; Martin, L. J.; Ramos, J.; Côté, J. (International Journal of Sports Science & Coaching, 2021)
The purpose of this study was to explore the association between coach leadership and the coach-athlete relationship. Eighty-one elite athletes (M = 20.4 years; SD = 3.8; 58% female and 42% male) responded to questionnaires pertaining to their coaches` leadership behaviours and the quality of their relationship. The overall model for predicting the quality of the coach-athlete relationship according to perceived coach leadership behaviours explained 61% of the variance. Three transformational leadership behaviours were positively associated with the quality of the coach-athlete relationship: individualized consideration, appropriate role-modelling, and fostering acceptance of group goals and teamwork. Based on a gender comparison, men perceived higher levels of leadership pertaining to role-modelling and intellectual stimulation, in addition to higher levels of quality for the coach-athlete relationship. This research emphasizes the importance of engaging in transformational leadership behaviours with regards to associations with perceptions of the coach-athlete relationship in elite sport contexts.